KEWAJIBAN DAN HAK SUAMI ISTRI (STUDI KOMPARASI PANDANGAN SAYYID MUHAMMAD ALAWI DAN K.H. HUSEIN MUHAMMAD) - M. Kemal Irsyadul I; Ibnu Djazari; Syamsu Madyan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
AbstractThe concept of husband and wife rights in jurisprudence discussion is very important in the detailed review and examined in this contemporary era. From the background, the composer tried to examine the two focus problems in this discussion, 1) how the concept of Sayheed Muhammad Alawi and KH. Husein Muhammad regarding the rights and obligations of husband wife. 2) How are the similarities and differences and their relevance to the rights and obligations of the husband wife with the applicable invitation in Indonesia. This type of research uses the Library Reseacrh (Literature Study). This type of research was conducted in the study and discussion of classical and contemporary literature literature. Especially the thought Sayheed Muhammad Alawi and KH Husein Muhammad as the object of this study .Based on the results of the research, the rights and obligations of husband and wife according Sayheed Muhammad Alawi about the concept detailed description and KH. Husein Muhammad about the concept concise description : muasyarah bilmakruf. The similarities are based on Al Quran and As-Sunah. Difference to understanding the Nash Al Quran and As Sunah with a different approach. Sayheed Muhammad Alawi Conservative-Tektualis. While KH. Husein Muhammad Progressive-kontektualis part of the second view of the figure is still relevant to the compilation of Islamic law, especially in pasal 83 and UU.No. 23 years 2003 ayat 9 KDRT. Keywords: Sayheed Muhammad Alawi, KH. Husein Muhammad, camparison, The rights and obligations husband wife